Implementation of School Field Introduction (PLP) on Basic Teaching Skills for Prospective Elementary School Teacher Students - AF Suryaning Ati MZ; Mochammad Miftachul Huda; Ahmad Ipmawan Kharisma (Jurnal Basicedu, 2022)
This study aims to determine the implementation and basic teaching skills of elementary school teacher education students, Faculty of Science, Technology, and Education, the University of Muhammadiyah Lamongan through school field introduction activities (PLP) in elementary schools. The approach used in this research is a quantitative form of One-Group Pretest-Posttest. Data collection techniques in this study using survey techniques. The results of the validity test of the PLP implementation instrument were declared valid and the reliability test was declared reliable with 0,746 > 0, 413 (r table)and the instrument for improving teaching skills is declared valid and the reliability test is declared reliable with 0,719 > 0, 413 (r table). The results of the PLP implementation test are 26.76, which means that the PLP implementation has gone very well following the hypothetical mean categorization value. While the results of the analysis of hypothesis testing using paired sample t-test obtained a significant value of 0.002 <0.05 so it can be concluded that there is an increase in students' basic teaching skills after carrying out School Field Introduction activities (PLP).